Third/ fourth degree perineal tear: does anorectal symptoms correlate with manometry and endo-anal scan result? - Abdulwahab, Dalia F; Md Nor, Azmi; Nusee, Zalina; Hussin, Hanim Yati; Ismail, Hamizah; Awang, Mokhtar; Ismail, Rozihan (Elsevier Ireland Ltd, 2014)
Introduction Obstetric anal sphincter injuries (OASIS) are the major cause of anal incontinence and can have a devastating effect on a woman’s quality of life (QoL). Despite identification and immediate repair of OASIS, the outcome is suboptimal. OASIS is reported in approximately 2.8% of primigravidae and 0.4 % of multigravidae. In this cohort study we assessed the short term outcome of OASIS primary repair which include anorectal symptoms, QoL, sphincter integrity and function.